2019
DOI: 10.1038/s41598-019-44459-x
|View full text |Cite
|
Sign up to set email alerts
|

Internalization, distribution, and activity of peptide H2 against the intracellular multidrug-resistant bovine mastitis-causing bacterium Staphylococcus aureus

Abstract: Bovine mastitis is mainly caused by Staphylococcus aureus , which is difficult to eliminate, prone to escape from antibacterial agents, and may cause recurring infections due to the intracellular nature of its infection and multidrug resistance. In this study, the intracellular activities of the NZ2114 derivative peptide H18R (H2) against methicillin-resistant S. aureus (MRSA) and multidrug-resistant bovine S. aureus strains were investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…In addition, many mechanisms of action between AMPs and virus molecules are still unclear and need to be further studied. However, we find it reasonable to assume that the previous fruitful findings and constructive theories from antibacterial studies with AMPs in vivo and in vitro, such as those concerning the mechanism of entry into the host cell and bactericidal details, might be shared and referenced during antiviral studies; it is confirmed from previous works that AMPs enter the blood circulation through different drug delivery routes, reach various organs, and further internalize into the cells through endocytosis and micropinocytosis [ 116 , 117 , 118 , 119 ]. Undoubtedly, wider and deeper new findings are highly deserving of anticipation and will attract great interest due to the unique advantages of AMPs, including their high penetration into the host cell owing to their intracellular origin, their close compatibility with the host, their hypersensitive early-warning/protection response to infection, and their low drug resistance rate owing to strong penetration and multitargeting of pathogens [ 30 , 120 , 121 , 122 , 123 , 124 , 125 ].…”
Section: Discussionsupporting
confidence: 70%
“…In addition, many mechanisms of action between AMPs and virus molecules are still unclear and need to be further studied. However, we find it reasonable to assume that the previous fruitful findings and constructive theories from antibacterial studies with AMPs in vivo and in vitro, such as those concerning the mechanism of entry into the host cell and bactericidal details, might be shared and referenced during antiviral studies; it is confirmed from previous works that AMPs enter the blood circulation through different drug delivery routes, reach various organs, and further internalize into the cells through endocytosis and micropinocytosis [ 116 , 117 , 118 , 119 ]. Undoubtedly, wider and deeper new findings are highly deserving of anticipation and will attract great interest due to the unique advantages of AMPs, including their high penetration into the host cell owing to their intracellular origin, their close compatibility with the host, their hypersensitive early-warning/protection response to infection, and their low drug resistance rate owing to strong penetration and multitargeting of pathogens [ 30 , 120 , 121 , 122 , 123 , 124 , 125 ].…”
Section: Discussionsupporting
confidence: 70%
“…S. aureus can internalize into host cells to form an intracellular pathogen pool, thereby avoiding being killed by traditional antibiotics and causing further damages (Al Kindi et al 2019;Wang et al 2019). Meanwhile, the bacterial cell wall component LTA is an important immunostimulatory virulence factor in S. aureus infections (Ginsburg 2002), can activate pro-inflammatory signaling (Rockel and Hartung 2012), and promotes the development of sepsis (Hotchkiss and Karl 2003).…”
Section: Discussionmentioning
confidence: 99%
“…S. aureus can internalize into host cells to avoid being killed by traditional antibiotics (Wang et al 2019). To explore the intracellular antimicrobial activity of ID13, MEECs prepared in DMEM free of antibiotics were dispensed in 12-well plates at 2.5 × 10 5 cells/mL and 750 μL/well.…”
Section: Intracellular Antimicrobial Activitymentioning
confidence: 99%
“…That might be the reason for the continuous attempt to develop vaccines against mastitis caused by S. aureus, which is yet to become successful (Côté-Gravel & Malouin 2019). A recent report suggested that NZ2114 derivative peptide, H18R (H2) can be used as a safe and potential candidate for treating S. aureus induced mastitis (Wang et al 2019). A study suggested that nasal immunization against S. aureus associated mastitis in bovines results in an increase level of anti-S. aureus specific IgA antibodies in milk and a negative correlation between anti-S. aureus specific IgA antibodies and numbers of S. aureus counts in the treated udder which may lead to the use of nasal vaccines in S. aureus associated mastitis (Nagasawa et al 2019) For the successful implementation of antibiotic usage in reduction of mastitis, there should be an increase in the diagnostic effort so that unnecessary antibiotic usage can be prevented (Krömker & Leimbach 2017).…”
Section: 1antibiotic Therapymentioning
confidence: 99%